Latent Mycobacterium tuberculosis Infection Is Associated With a Higher Frequency of Mucosal-Associated Invariant T and Invariant Natural Killer T Cells - Paquin-Proulx, Dominic; Costa, Priscilla R.; Terrassani Silveira, Cassia G.; Marmorato, Mariana P.; Cerqueira, Natalia B.; Sutton, Matthew S.; O’Connor, Shelby L.; Carvalho, Karina I.; Nixon, Douglas F.; Kallas, Esper G. (Frontiers in Immunology, 2018)
Increasing drug resistance and the lack of an effective vaccine are the main factors contributing to Mycobacterium tuberculosis (Mtb) being a major cause of death globally. Despite intensive research efforts, it is not well understood why some individuals control Mtb infection and some others develop active disease. HIV-1 infection is associated with an increased incidence of active Tuberculosis (TB), even in virally suppressed individuals. MAIT and iNKT cells are innate T cells that can recognize Mtb-infected cells. Contradicting results regarding the frequency of MAIT cells in latent Mtb infection have been reported. In this confirmatory study, we investigated the frequency, phenotype, and IFNγ production of MAIT and iNKT cells in subjects with latent or active Mtb infection. We found that the frequency of both cell types was increased in subjects with latent Mtb infection compared to uninfected individuals or subjects with active infection. We found no change in the expression of HLA-DR, PD-1, and CCR6, as well as the production of IFNγ by MAIT and iNKT cells, among subjects with latent Mtb infection or uninfected controls. The proportion of CD4-CD8+ MAIT cells in individuals with latent Mtb infection was, however, increased. HIV-1 infection was associated with a loss of MAIT and iNKT cells, and the residual cells had elevated expression of the exhaustion marker PD-1. Altogether, the results suggest a role for MAIT and iNKT cells in immunity against Mtb, and show a deleterious impact of HIV-1 infection on those cells.